2016
DOI: 10.1186/s13098-016-0135-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with glucose tolerance, pre-diabetes, and type 2 diabetes in a rural community of south India: a cross-sectional study

Abstract: BackgroundIndia’s national rural prevalence of type 2 diabetes has quadrupled in the past 25 years. Despite the growing rural burden, few studies have examined putative risk factors and their relationship with glucose intolerance and diabetes in rural areas. We undertook a cross-sectional study to determine the prevalence of impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and type 2 diabetes in a rural area of south India. In addition, we determined which factors were associated with type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 44 publications
(68 reference statements)
6
38
0
Order By: Relevance
“…15 These figures imply that though the prevalence of DM varies in different settings, it is certainly quite high and warrants immediate attention. Our study adds to the limited but growing body of evidence suggesting that diabetes is no longer confined to urban areas of India and is a matter of concern in rural areas as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 These figures imply that though the prevalence of DM varies in different settings, it is certainly quite high and warrants immediate attention. Our study adds to the limited but growing body of evidence suggesting that diabetes is no longer confined to urban areas of India and is a matter of concern in rural areas as well.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have also found a positive association with family history, hypertension and overweight with Diabetes. [14][15][16][17][18] More than one third of the people were found to have random blood sugar more than 140 mg/dl indicating high proportion of population at risk of developing diabetes in future if preventive measures including life style modification are not followed.…”
Section: Discussionmentioning
confidence: 99%
“…26 Little et al found the prevalence of newly diagnosed diabetics in rural Kerala to be 41.8% of total diabetics. 27 This high prevalence of undiagnosed diabetics might have emphasized upon poor healthcare-seeking behaviour of the study population.…”
mentioning
confidence: 95%
“…5 Little et al, in a rural community in south India showed prevalence of 10.8%. 3 Ghorpade et al, at rural Pondicherry found T2DM prevalence of 5.8%. 6 The ICMR INDIAB study showed rural prevalence of T2DM in rural Tamil Nadu as 7.8%, Maharashtra 6.5%, Jharkand 3%, Chandigarh 8.3%.…”
Section: Introductionmentioning
confidence: 93%
“…The reason for this increasing diabetes burden is attributed to modernization and urbanization. 3 Majority of the population in India reside in the rural areas approximately 742 million. Hence, the estimation of the prevalence of diabetes in rural India becomes crucial from the point of view of designing the strategies to halt the rising prevalence of diabetes.…”
Section: Introductionmentioning
confidence: 99%